The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1096348020944460
|View full text |Cite
|
Sign up to set email alerts
|

A Reflective–Formative Hierarchical Component Model of Perceived Authenticity

Abstract: Discussions on authenticity have become prominent in tourism research, particularly in the context of heritage tourism and quantitative approaches have become popular methods to investigate authenticity, especially from a tourist’s perspective. Previous studies, however, have failed to include multiple forms of authenticity into a single quantitative scale, as well as to use a formative approach for its measures. This study develops a comprehensive and reliable scale of authenticity, considering its multidimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Studies suggested that tourists' perception of authenticity is based on tangible and intangible factors. The former includes exterior features and interior decoration of buildings, as well as surrounding environment and ambience in tourism attractions/destinations [28][29][30][31]. The intangible factors are mainly customs and traditions, such as clothing, food, art, stories, festivals and cultural rituals.…”
Section: Object-based Authenticity and Existential Authenticity In Tomentioning
confidence: 99%
“…Studies suggested that tourists' perception of authenticity is based on tangible and intangible factors. The former includes exterior features and interior decoration of buildings, as well as surrounding environment and ambience in tourism attractions/destinations [28][29][30][31]. The intangible factors are mainly customs and traditions, such as clothing, food, art, stories, festivals and cultural rituals.…”
Section: Object-based Authenticity and Existential Authenticity In Tomentioning
confidence: 99%
“…The measurement of the authentic experience refers to the research of Nguyen (2015, 2020) et al [14,28,29], 8 items, including responses such as the following: "I felt the real way of life of the local residents", "I could experience local traditional cultures", "The overall architecture and exhibits reflect actual buildings of the past", "a calm and peaceful atmosphere is created here", "rural tourism creates opportunities for selfdiscovery", "through rural tourism, I can break through the limitations of daily routines", "through rural tourism, I realize the psychological needs of satisfaction", and "through rural tourism, I can get along with others more harmoniously".…”
Section: Methodsmentioning
confidence: 99%
“…Surveys with the response of “Never been to” were considered invalid. The scale of co-creation behavior was adapted from Campos et al (2017); constructive authenticity was from Nguyen (2020); existential authenticity of intrapersonal and interpersonal dimensions was adapted from Yi et al (2022); the measurement of memorability was from Oh et al (2007); and revisit intention was from Zhang et al (2016). Except for the respondents’ demographics and the screening item, the items were scored on a seven-point Likert scale ranging from 1 (strongly disagree) to 7 (strongly agree); the survey comprised 44 items in total.…”
Section: Study 2: Validating Construct Validity Of the Model And Test...mentioning
confidence: 99%